Game Tude Force Berbasis Android - Kadek Wikan Paramasila; Padma Nyoman Crisnapati; Made Windu Antara Kesiman; I Gede Mahendra Darmawiguna (Universitas Pendidikan Ganesha, 2014)
In addition as a means of entertainment, Tude Force Game also aims to raise as well as to introduce the Ramayana story that has begun to be forgotten to the public. Another aim is to provide insight on the Android Operating System without forgetting culture embodied in the traditional stories just like the Ramayana. Tude Force game is designed on Android Operating System. This game is created using Adobe Flash CS 3 which then converted into HTML 5 so it can be played in android operating system and PC. To illustrate the use of relationship between the user and the software, Block Diagram is used as the flow of data transfer. To support the completion of the system design in Tude Force AndroidBased Game, the author uses the stages of the waterfall model. Results that can be achieved from the process of making Tude Force game is that this game can be played in the android operating system which is integrated in Samsung Tab 3 GT hardware. Besides using android, Tude Force game can also be played on a PC through browser